Trophic interactions and diel feeding rhythms of microzooplankton in a productive Swedish Fjord. (3rd September 2020) - Arias, Anna; Saiz, Enric; Tiselius, Peter; Calbet, Albert
Abstract: Microzooplankton play a pivotal role in the energy transfer between lower and upper trophic levels in marine planktonic food webs. While laboratory data suggest that microzooplankton exhibit higher feeding rates during the daytime, evidence from the field is scarce and contradictory. In this study, we first characterized the nano- and microplanktonic communities of the Gullmar Fjord (Sweden) and its environmental conditions during July and August 2017. Then, we explored the grazing impact of microzooplankton on the phytoplankton community of this ecosystem and assessed their diel grazing activity using the dilution technique. Finally, we evaluated the impact of mesozooplankton at natural concentrations during the experiments. Microzooplankton removed 26% of the phytoplankton standing stock and 96% of the primary production daily, while mesozooplankton did not exert a significant impact on microplankton activity. We did not detect significant diel microzooplankton grazing rhythms during the first experimental period; however, during the second part of the study, after an upwelling event, grazing rates were significantly higher during the night. Therefore, the microzooplankton grazing rhythm in natural systems may vary according to the species composition and abundances of both microzooplankton and prey communities.